Ear Deformities in Children - Nikolai A. Daikhes; Khassan M. Diab; Dmitry S. Kondratchikov; Olga A. Pashchinina; Liudmila V. Balakina ("Paediatrician" Publishers LLC, 2022)
Ear deformities occur in 5-50% of newborns [1, 2]. Usually ear deformities minimally affect hearing, however, they can lead to psychological disorders, anxiety, social isolation, and behavioral problems. Ear deformities can spontaneously self-correct without any treatment in about 30% of cases. Surgical or non-surgical correction of ears' shape is the only alternative for the rest of the patients. Molding is an effective method for non-surgical correction of ear deformations. It is possible to achieve better treatment results if you start the procedure during the first days of life due to sufficient plasticity of ear cartilage in newborns. Otherwise, otoplasty would be necessary at the age of 3-6 years.